Đánh giá của giáo viên Ngữ văn cấp trung học phổ thông về tích hợp dạy kĩ năng đọc - viết văn bản nghị luận văn học: khảo sát tại khu vực Đồng bằng sông Cửu Long - Nguyễn, Thanh Liêm; Nguyễn, Thị Hồng Nam (Tạp chí Giáo dục, 2025)
The 2018 Vietnamese Literature Curriculum and the new textbooks emphasize integrated teaching, particularly the integration of reading and writing skills. Numerous studies have confirmed the close relationship between these two skills and the effectiveness of integration in enhancing writing competence. However, in teaching literary argumentative texts at the upper secondary level, reading and writing are still often taught separately, reducing the effectiveness of language development. This study surveys the opinions of 152 high school Literature teachers in the Mekong Delta region to clarify the current situation, perceived advantages and barriers, and teachers’ suggestions related to the integration of reading and writing skills. The findings indicate that teachers still lack awareness and skills in designing integrated activities; teaching materials and equipment remain limited; and students face difficulties in transferring from reading to writing. Therefore, it is necessary to strengthen professional training, develop digital learning resources, organize thematic workshops, and invest in supportive teaching equipment. Teachers also need to make effective use of textbooks and foster argumentative analysis skills during reading lessons to lay the foundation for writing activities.